Lifesaving Intraosseous Access in a Patient with a Massive Obstetric Hemorrhage - Joey de Vogel; Roger Heydanus; Annemarie G.M. Mulders; Dina J.C. Smalbraak; Dimitri N.M. Papatsonis; Bastiaan M. Gerritse (Thieme Medical Publishers, Inc., 2011)
A 42-year-old, gravida 1, para 0 woman was induced at a gestational age of 41 weeks because of post-term dates. The fourth stage of delivery was complicated by a massive hemorrhage. The uncontrollable persisting amount of blood loss led to hypovolemic shock and cardiopulmonary arrest. Lifesaving extra access was gained through an intraosseous needle in the proximal tibia. We therefore advocate including the use of an intraosseous needle as an additional route for intravascular volume replacement in case of peripartum hemorrhage.